ANALISIS KINERJA EKSPOR DAN IMPOR TEMBAKAU INDONESIA PERIODE 2000-2009 - Luthfi Safitri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2011)
Writing this thesis aims to find and to anlysis Indonesia tobacco export and import facing global crisis.Based on Indonesia export and impor in 2000-2009. Variabel in this thesis is Indonesia tobacco.Variabel in this thesis in 2000-2009. The method in this thesis is market consentration (KP) Revealed Comparative Advantage (RCA) and Trade Specialization Ratio (TSR). From analysis Regresion in 2000-2009 show that export and import from TSR methode that Indonesia comparative advantages,tobacco can compet with another country in the world.Keywords: Tobacco,Indonesia Expor, Import